Noise-resilient single-pixel compressive sensing with single photon counting - Lili Li; Santosh Kumar; Yong Meng Sua; Yu-Ping Huang (Communications Physics, 2024)
Abstract The fast expansion of photon detection technology has fertilized the rapid growth of single-photon sensing and imaging techniques. While promising significant advantages over their classical counterparts, they suffer from ambient and quantum noises whose effects become more pronounced at low light levels, limiting the quality of the acquired signal. Here, we study how photon-counting noises degrade a single-pixel optical classifier via compressive sensing, and how its performance can be restored by using quantum parametric mode sorting. Using modified National Institute of Standards and Technology (MNIST) handwritten digits as an example, we examine the effects of detector dark counts and in-band background noises and demonstrate the effectiveness of mode filtering and upconversion detection in addressing those issues. We achieve 94% classification accuracy in the presence of 500 times stronger in-band noise than the signal received. Our results suggest a robust and efficient approach to single photon sensing in a practical environment, where sunlight, ambient, and multiscattering noises can easily dominate the weak signal.